A Neonate with Non-immune Hydrops Foetalis in Rh Non-immunized Mother - Begum, Nurjahan; Kazal, Rezaul Karim; Anwary, Shaheen Ara; Nahar, Khadiza Nurun; Shamsunnahar, Parveen Akhter; Akhter, Nargis (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v34i2.10221 BJCH2010; 34(2): 70-72